2020
DOI: 10.1155/2020/8880974
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Engineering Properties of Metakaolin Based Concrete: Towards Combatting Chloride Attack in Coastal/Marine Structures

Abstract: Changing human lifestyle and increasing urbanisation are contributory factors to the high demand for concrete construction materials across the globe. With the imminent developments in the unpopulated marine/coastal zones, higher installation of concrete facilities is still expected. However, poor design and construction procedures coupled with inadequate materials selection and exposure to aggressive environmental conditions, such as chloride laden environments, often result in the reduced aesthetic and struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 28 publications
4
27
0
Order By: Relevance
“…Increased [46,47] Improved [63] Setting time increased [63,64] Reduced [60,61] Silica Fume Increased at lower replacement but decreased at higher replacement [50] Improved when lesser percentage is added [59] Prolonged the setting time [66] Reduced [59] GGBFS Increased [52,53] Decreased [58] Setting time delayed [56] Higher content of GGBFS increased the segregation and bleeding [58] journal.ump.edu.my/construction ◄ Decreased with the increment of metakaolin in concrete [67] Workability of concrete reduced [64,65] Setting time reduced [64,67] Reduced [67] Agriculture waste (Rice husk ash, sawdust ash etc) Decreased [48,54] Workability Reduced [54] Increased [69] Reduced [69] Domestic waste (glass, plastic)…”
Section: Waste Materials Slump Values Workability Setting Time Segreg...mentioning
confidence: 99%
“…Increased [46,47] Improved [63] Setting time increased [63,64] Reduced [60,61] Silica Fume Increased at lower replacement but decreased at higher replacement [50] Improved when lesser percentage is added [59] Prolonged the setting time [66] Reduced [59] GGBFS Increased [52,53] Decreased [58] Setting time delayed [56] Higher content of GGBFS increased the segregation and bleeding [58] journal.ump.edu.my/construction ◄ Decreased with the increment of metakaolin in concrete [67] Workability of concrete reduced [64,65] Setting time reduced [64,67] Reduced [67] Agriculture waste (Rice husk ash, sawdust ash etc) Decreased [48,54] Workability Reduced [54] Increased [69] Reduced [69] Domestic waste (glass, plastic)…”
Section: Waste Materials Slump Values Workability Setting Time Segreg...mentioning
confidence: 99%
“…Previous studies have shown that increased SiO2 contents are expected when kaolin transforms into MK through heat treatment. The SiO2 contents can vary from 50 to 60%, sometimes reaching 74.3% (Fadzil et al, 2017;Pillay et al, 2020;Rashad, 2013;Sullivan et al, 2018). The remainder consists of kaolinite and a small amount of muscovite.…”
Section: Crystallinity and Functional Groupsmentioning
confidence: 99%
“…1 a Fly ash; b silica fume; c GGBS; d rice husk ash; e bagasse ash; and f coconutbased waste ash [5][6][7] agricultural and food wastes as shown in Fig. 3b [17][18][19][20][21]. Various studies have been and are being conducted on the utilization of industrial wastes in concrete production.…”
Section: Introductionmentioning
confidence: 99%